ASSESSMENT OF COUNSELLORS’ AWARENESS AND PERCEPTIONS OF E-THERAPY FOR IMPROVED GUIDANCE AND COUNSELLING SERVICES IN SOUTHWEST ZONE, NIGERIA: ASSESSMENT OF COUNSELLORS’ AWARENESS AND PERCEPTIONS OF E-THERAPY FOR IMPROVED GUIDANCE AND COUNSELLING SERVICES IN SOUTHWEST ZONE, NIGERIA - DUROWOJU, ESTHER; DUROWOJU, ESTHER; Olaleye, Victor (African Journal of Behavioural and Scale Development Research, 2025)
ABSTRACT Counselling in the 21st has revolutionized to e-therapy as against the face-to-face relationship that characterized counselling before this dispensation. Therefore, this study investigated the extent of counsellors’ awareness and perceptions of e-therapy for improved guidance and counselling in Southwest zone of Nigeria. Descriptive research design which is ex- post facto type was adopted. The counselling psychologists in both Universities and secondary schools in the Southwest zone constituted the population and 78 counselling psychologists were purposively used for the study. A questionnaire was adopted and the reliability coefficients were 0.82, 0.78 and 0.72 respectively determined using Cronbach Alpha. Data were analyzed using descriptive (frequency, percentages, mean and content analysis) and inferential analysis (t-Test). Findings revealed that the rate of counsellors who was aware of e-counselling was moderately high (π = 2.77); there was no significant difference between male and female counsellors’ awareness of the use of technology for counselling services [t (76) = 0.229 p > 0.05]. The rate of those who were competent in the use of e-therapy was moderately low (π = 2.48), there was no significant difference between male and female counsellors’ competency in the usage of technology for counselling services [t (76) = 1.416 p > 0.05] while the rate of those who frequently utilize e-therapy was very low. Recommendations made were: counsellors should update their knowledge of e-therapy, acquire digital skills and cyber security should be improved to guarantee confidentiality in the provision of guidance and counselling services among others. Keywords: Guidance, Counselling, E-therapy, Generation Z